TARGET SUBSIDIES AS A FILM SCREENING DEVELOPMENT TOOL IN RUSSIAN REGIONS - L. A. Lanina; A. V. Malyshev (Вестник университета)
Execution of protectionist measures by the state in the film screening field is a significant for the entire film industry as a whole, as the state of the Russian film screening affects both distribution and film production. The implementation process of the state program to provide subsidies for the cinemas modernization cinemas in small and medium-sized Russia cities has been examined. The current program results, their importance for the regional film screening and the Russian film industry have been analyzed. The special socio-economic conditions of the subsidized theaters functioning have been highlighted. The two-level system organization for further activities subsidized cinemas support is proposed and a measures set to achieve the state program goals for the long term have been offered.